Water allocation policies for the Dong Nai River Basin: an integrated perspective - Ringler, Claudia; Vu Huy, Nguyen; Msangi, Siwa (Wiley, 2006)
Recent water sector reforms and increased scarcity and vulnerability of water resources, combined with declining public funding available for large scale infrastructure investment in the sector, have led to a greater awareness by the Government of Vietnam for the need to analyze water resource allocation and use in an integrated fashion, at the basin scale, and from a perspective of economic efficiency. In this study we focus on the development, application, and selected policy analyses using an integrated economic hydrologic river basin model for the Dong Nai River Basin in southern Vietnam. The model framework depicts the sectoral structure and location of water users (agriculture, industry, hydropower, domestic, and the environment) and the institutions for water allocation in the basin. Water benefit functions are developed for the major water uses subject to physical limitations and to constraints of system control and policy. Based on this modeling framework, we will analyze policies that can affect water allocation and use at the basin level, including both basin-specific and general macroeconomic policies